Elicitor-Induced VOC Emission by Grapevine Leaves: Characterisation in the Vineyard - Christelle Lemaitre-Guillier; Agnès Chartier; Christelle Dufresne; Antonin Douillet; Stéphanie Cluzet; Josep Valls; Nicolas Aveline; Xavier Daire; Marielle Adrian (Molecules, 2022)
The present study is aimed at determining whether leaf volatile organic compounds (VOCs) are good markers of the grapevine response to defence elicitors in the field. It was carried out in two distinct French vineyards (Burgundy and Bordeaux) over 3 years. The commercial elicitor Bastid® (Syngenta, Saint-Sauveur, France) (COS-OGA) was first used to optimise the VOCs’ capture in the field; by bagging stems together with a stir bar sorptive extraction (SBSE) sensor. Three elicitors (Bastid®, copper sulphate and methyl jasmonate) were assessed at three phenological stages of the grapevines by monitoring stilbene phytoalexins and VOCs. Stilbene production was low and variable between treatments and phenological stages. VOCs—particularly terpenes—were induced by all elicitors. However, the response profiles depended on the type of elicitor, the phenological stage and the vineyard, and no sole common VOC was found. The levels of VOC emissions discriminated between weak (Bastid® and copper sulphate) and strong (methyl jasmonate) inducers. Ocimene isomers were constitutively present in the overall blends of the vineyards and increased by the elicitors’ treatments, whilst other VOCs were newly released throughout the growing seasons. Nonetheless, the plant development and climate factors undoubtedly influenced the release and profiles of the leaf VOCs.